Transforming family planning services in the Latin American and Caribbean region - Helzner, Judith F. (2002)
Uses qualitative data analysis to review the experience of nine family planning association projects in the Latin American and Caribbean region, that have made a successful organizational transition from services focused on family planning, to a gender-based and sexual health approach.